Recent Progress of Silicon Photonics for Middle-Infrared Application - Haowen Shu; Zhaotang Su; Xingjun Wang; Zhiping Zhou (Dianxin kexue)
“Capacity Crunch”in NIR field needs to be forestalled since the pressure of information transmission，processing and storage is continually growing.Silicon photonics，with compatibility of CMOS，compact structure and low fabrication cost，shows its superiority in the field of mid-IR transmission and signal processing.Thus a lead forward is excepted to be realized in large-scale integration of mid-IR devices and nonlinear optical and other field.The strengths and challenge of silicon photonics in mid-IR application were estimated firstly.Then some“building block”components of silicon photonics in mid-IR（waveguides，beam splitter/combiner，diode，etc）were introduced.Achievements of devices （nonlinear optical devices based on FWM，frequency comb in sensing field and laser，modulator，detector in communication field）within the last five years were presented.Finally，the conclusion was made for recent research progress.